The usability and applicability of Porter’s Generic Strategies typology in a retail context, with regard to consumer perceptions on value. - Gindy, Andrew (2012)
While Porter’s Generic Strategies are a widely accepted typology of strategic options for businesses in most contexts, previous studies linking the framework to the retail industry are not as widely seen. The purpose of this project is to approach the subject area to analyse whether retail Multinational Enterprises in today's economic climate adhere to the principles Porter outlines in his seminal framework, or, if they combine all elements of his typology in order to provide consumers with a distinct ‘value-orientated’ service. The consumer perception dimension of this study adds force to the overall conclusions as it can clearly depict whether a firm’s intended output matches its actual output.